PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI IPAS INDONESIAKU KAYA HAYATINYA DI KELAS V SD NEGERI OEBOBO 1 KOTA KUPANG - Delphy Martni Selan; Maxsel Koro; Kurniayu T. R. A. Ratu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study, conducted by Delphy Martni Selan, is entitled “The Use of Problem- Based Learning Model Assisted by Video Media to Improve Student Learning Outcomes on the IPAS material ‘My Indonesia is Rich in Biodiversity” in Class V of SD Negeri Oebobo 1, Kupang City”. The pusose of the research was to improve student learning outcomes through the application of the Problem-Based Learning model supported by video media. The research question was: How can the use of the Problem-Based Learning model assisted by video media improve student learning outcome on the IPAS material “My Indonesia, Rich in Biodiversity”? This research employed Classroom Action Research (CAR), which consisted of four stages: planning, implementation, observation and tests, and reflection. The subjectsof the study were 34 fifth-grade students of SD Neger Oebobo 1. Data were collected through observation and test tec hniques, and anlyed using descriptive qualitative and quantitative approaches. The findings indicated that in cycle I, 25 students (74%) achieved mastery, while 9 students (26,47%) didi not. Students who suceeded paid attention to the teacher’s explanation, cooperatedin groups, presented discussion results, and were able to compete worksheets and test corrrectly. Meanwhile, students who failed tended to be inatentive, played during lesson, and were unable to complete worksheets or tests properly. In cycle II, significant improvement was observed, with 32 students (94%) achieving mastery. These students demonstrated greater focus, stronger collaboration, active participation in discussions, confidence in completing evaluation tests. However, 2 students (5,88%) had not yet achieved mastery, as they were self- focused and less attentive to the teacher’s explanations.